2000
DOI: 10.1016/s0893-133x(99)00136-0
|View full text |Cite
|
Sign up to set email alerts
|

Differential Behavioral Effects of Plasma Tryptophan Depletion and Loading in Aggressive and Nonaggressive Men

Abstract: Preliminary findings indicate that men with high trait hostility may be prone to aggression increases following plasma tryptophan (Trp) depletion. We measured laboratory aggression in men selected for presence (n ϭ12Substantial research has implicated decreased serotonin (5-HT) neurotransmission in human aggressive behavior (Brown et al. 1979;Coccaro et al. 1997a;Linnoila et al. 1983;Virkkunen et al. 1994). In recent neuroendocrine challenge studies, aggression has correlated negatively with plasma prolactin (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
83
1
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(97 citation statements)
references
References 73 publications
10
83
1
3
Order By: Relevance
“…It is consistent with other work showing that ATD affects impulsive behavior only in certain individuals (Cherek and Lane, 1999;LeMarquand et al, 1999;Bjork et al, 2000;Marsh et al, 2002;Swann et al, 2002; but see Crean et al, 2002).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It is consistent with other work showing that ATD affects impulsive behavior only in certain individuals (Cherek and Lane, 1999;LeMarquand et al, 1999;Bjork et al, 2000;Marsh et al, 2002;Swann et al, 2002; but see Crean et al, 2002).…”
Section: Discussionsupporting
confidence: 92%
“…CSF concentrations of the 5-HT metabolite 5-HIAA correlate inversely with impulsive behaviors in many neuropsychiatric and personality disorders including aggressive, conduct, and attention-deficit/hyperactivity disorders (Evenden, 1999). Furthermore, recent studies with human volunteers have found that ATD increases impulsive and aggressive behavior, although these effects appear to depend on individual differences in impulsive personality traits (Cherek and Lane, 1999;LeMarquand et al, 1999;Dougherty et al, 1999;Bjork et al, 2000;Marsh et al, 2002;Crean et al, 2002). Findings from studies with clinical human populations are corroborated by an extensive number of animal studies, which suggest that impulsive choice in delaydiscounting paradigms and premature responding in choice reaction-time tasks implicate changes in the 5-HT system (Wogar et al, 1993;Harrison et al, 1997a, b;Puumala and Sirvio, 1998;Koskinen et al, 2000;Mobini et al, 2000;Dalley et al, 2002;Passetti et al, 2003;Winstanley et al, 2003;Liu et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies using normal males have reported conflicting results under Trp depletion (Bjork et al 1999;Moeller et al 1996;Pihl et al 1995;Smith et al 1986); for example, high-trait aggressive men have shown increases in both subjective paperand-pencil measures and in laboratory-measured behavioral aggression under Trp depletion, whereas lowtrait aggressive men have not (Cleare and Bond 1995). In our most recent laboratory studies (Bjork et al 1999(Bjork et al , 2000, Trp depletion increased aggressive behavior in men with high baseline levels of aggression but did not affect men with low baseline levels.Most studies of the relationship between CNS 5-HT function and aggressive/impulsive behaviors have relied on men. In our laboratory, we are conducting a series of systematic analyses of aggressive/impulsive behavior of women using a paradigm (PSAP, see below) to prospectively measure changes in aggressive responding as a result of experimental manipulation.…”
mentioning
confidence: 63%
“…This indirectly supports the lack of effect of serotonin in the control of stopping because there are links between serotonin and some, although not all, forms of aggression. For example, serotonin depletion using ATD may increase aggression in subjective assessment and in laboratory tests such as the Point Subtraction Aggression Paradigm and Taylor Competitive Reaction Time Task (Bjork et al 1999(Bjork et al , 2000Cleare and Bond 1995;Moeller et al 1996;Pihl et al 1995;Salomon et al 1994).…”
Section: Role Of 5-ht In Action Cancellationmentioning
confidence: 99%